Effect of different types of mulching on biochemical parameters of tomato (Solanum lycopersicum) - PINDER, ROHIT; RANA, RENU (The Indian Journal of Agricultural Sciences, 2016)
Different mulching treatments consisting of two inorganic (black polythene, white polythene) and four organic mulches (FYM, rice straw, dry leaves, sugarcane trash) along with control (without mulching) were used to study their effect of biochemical parameters in two tomato (Solanum lycopersicum L.) varieties (Cherry tomato and Marglobe). The experiment was conducted at Research Area, Department of Horticulture, DCAST, Selaqui, Dehradun (Uttarakhand) during 2013-2014. Experiment was laid out in factorial randomized block design with seven treatment combinations and each treatment was replicated thrice. It was observed that among all the treatments black polythene mulch showed significantly higher TSS (6.78 0Brix and 6.64 0Brix) and lycopene content (0.39 mg/kg and 0.38 mg/kg) in Cherry tomato and Marglobe varieties. The pH of immature (4.43, 4.57) and mature fruits (4.23, 4.23) was found higher with sugarcane trash mulch in both the varieties followed by other mulches. Among all the treatments, black polythene mulch was found to be the best for tomato cultivation.